Digital Banking Policies and Regulations For Sharia Banking in Indonesia - Siti Anifah; Shelvyna Rikantasari (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
In accordance with current developments in information technology, the services offered by banks are growing and leading to digital services. The demand for digitization of banking operations is also driven by changes in business life which are now dominated by the millennial generation who prefer the convenience of online transactions through digital platforms. The digital banking transformation process is also accelerated by the emergence of new competitors, such as non-bank financial service providers, often called fintech. The purpose of this research is to find out the regulation of digital banking law in Indonesia and the urgency of digital banking regulations for Islamic banking in Indonesia. The method used is descriptive qualitative with a library research approach to track event log data, which is then used by the author to collect data including sources from previous studies. The results and conclusions of this study are that digital banking provisions have been regulated in the Financial Services Authority Regulation No.12/POJK.03/2018 concerning the Implementation of Digital Banking Services by Commercial Banks. The urgency of establishing digital banking regulations for Islamic banking in Indonesia is the rampant mode of digital crime (Cyber ​​crime) which can disrupt the convenience and security of customer data. This is because there are no regulations that strictly regulate such as laws to specifically regulate Islamic digital banking. Digital banking law is only regulated in OJK Regulations, so it has not been able to overcome problems, especially in the implementation of digital banking for Islamic banking given the weak binding force of these Regulations.